2006
DOI: 10.1371/journal.pone.0000085
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Mammalian Gene Families

Abstract: Gene families are groups of homologous genes that are likely to have highly similar functions. Differences in family size due to lineage-specific gene duplication and gene loss may provide clues to the evolutionary forces that have shaped mammalian genomes. Here we analyze the gene families contained within the whole genomes of human, chimpanzee, mouse, rat, and dog. In total we find that more than half of the 9,990 families present in the mammalian common ancestor have either expanded or contracted along at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
248
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(274 citation statements)
references
References 57 publications
(84 reference statements)
19
248
3
1
Order By: Relevance
“…Human-specific patterns of alternative splicing have been found to be particularly widespread within the brain (50). Also, it has been estimated that humans and chimpanzees differ by at least 6% in their complement of genes (51). The trichromatic visual system is one of the dramatic specializations present in the human lineage compared with other mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Human-specific patterns of alternative splicing have been found to be particularly widespread within the brain (50). Also, it has been estimated that humans and chimpanzees differ by at least 6% in their complement of genes (51). The trichromatic visual system is one of the dramatic specializations present in the human lineage compared with other mammals.…”
Section: Discussionmentioning
confidence: 99%
“…A model for the evolution of the HBA genes in the European rabbit Recent studies have highlighted the fast rate of gene gain and loss in the multigene families of many mammalian species (Demuth et al, 2006;Hahn et al, 2007;Hoffmann et al, 2010). The pattern of gene turnover has been especially well characterized in the a-globin gene cluster of mammals (Zimmer et al, 1980;Hoffmann et al, 2008a;Storz et al, 2008).…”
Section: Copy Number Polymorphism and Hybridization R Campos Et Almentioning
confidence: 99%
“…Recent studies have found that such large-scale mutations can have dramatic evolutionary and phenotypic consequences. Comparative genomic studies have revealed that changes in gene copy number caused by duplication and deletion events are often adaptive (Demuth et al 2006) and suggest that gene duplication events can result in the evolution of new gene functions [e.g., the excess of d N /d S ratios .1 in young gene duplicates observed in Kondrashov et al (2002) and Zhang et al (2003)]. In addition, large duplications and deletions segregating within populations, often referred to as copy-number variants (CNVs), have been shown to be both beneficial (Perry et al 2007;Turner et al 2008;Kolaczkowski et al 2011) and deleterious (McCarroll and Altshuler 2007;Stankiewicz and Lupski 2010;Girirajan et al 2011); these polymorphisms are widespread in Drosophila (Emerson et al 2008;Langley et al 2012).…”
mentioning
confidence: 99%